THE SOUND DIMENSION IN THE UPPER BASIN OF THE MIÑO RIVER (GALICIA, NW IBERIAN PENINSULA): CHARACTERIZATION AS A WATER HERITAGE (Environmental Smoke, 2021)
The sound spectrum of water configures representative marks of various environments, which define a sound heritage with scientific, cultural, emotional, sensorial and educational value. From this perspective, river environments comprise a wide spectrum of sonic resonances. This study, contextualized within the field of geo-sonority research, considers the recording and analysis of water through several samples from the upper basin of the Miño River. The objectives are to advocate for the role of sonority as part of the intangible heritage, to explore its character in the fluvial environment of inland Galicia, and to contribute to the preservation of the sonic marks of water as sounds inherent to the identity of an area. The methodology applied consists of phases of field recording, the creation of databases and of phonic analysis. Water in its sound form, from the drop rhythmically repeating to the roar of a waterfall, fills an audible sound spectrum that characterizes soundscapes. By registering, documenting, and analyzing the sounds of the water, we advance in the knowledge of the diversity of the sound environments in the river basin of the Miño River.